“Massa’an Jhuko’ Se Sae Khas Situbendeh” Katalog Fotografi Essai Makanan Khas Situbondo Sebagai Media Informasi - Luky Lebrya Yanuarta; Handry Rochmad Dwi Happy (Jurnal Desain Komunikasi Visual Asia, 2022)
This study discusses photo essays that tell of an incident where the process from beginning to end of processing Situbondo typical food in the form of processed seafood is visualized in the form of a photo essay catalog image. In this study, there are 5 typical Situbondo foods. From these 5 special foods, a photo essay catalog book was made as a means that can represent limited information and become a source of information to increase the knowledge of people outside Situbondo about typical foods made from marine fish in Situbondo Regency to preserve them so that they are not lost to time. This catalog book will later become one of the printed media that will be placed in the Situbondo Library to make it easier for visitors and the local community to know and understand Situbondo's special food. Of the questionnaires distributed to 30 respondents as much as 90.33% stated that the selection of photo catalog media strongly agreed and was in accordance with the target so that with the existence of this catalog book it had answered the problem formulation. Keywords: catalog, photography, “massa’an jhuko”.